Customer’s perception towards buying Chinese products: an empirical investigation in Malaysia - Sarwar, Abdullah Al-Mamun; Azam, S. M Ferdous; Haque, A. K. M. Ahasanul; Sleman, Ghassan; Nikhashemi, Seyed Rajab (IDOSI Publication, 2013)
The emergence of Chinese products and its growing popularity has been a phenomenon for social science researchers. In addition, the “cheap” image of Chinese products together with their product quality have raised the issue to investigate further why customers buy Chinese products and what they perceive before buying. A number of studies already been conducted on the effect of country-of-origin image on customers’ purchase behavior which are mostly in the context of developed countries. Hence, this study attempts to fill the gap that rarely been studied on the consumer’s perception towards buying Chinese products especially on the Malaysian context. The present study has enhanced the understanding of how the customers perceive the Chinese products while making the buying decision. It explores how different perception tools can positively influence their purchase decision. In addition, this study provides practical insights into how the customers use and perceive different product information in different perspectives which may be alien to their cultural background. This study suggests that, the Malaysian consumers are very conscious about quality and price of Chinese products. Therefore, marketers of Chinese product in Malaysia should be very careful about the price, quality and technology advancement of product they are offering in the market place. Finally, although many significant findings have been reported in this study, there are several other tangible and intangible issues that can be improved in future studies.